Aplicação da manutenção centrada na confiabilidade para mitigação de falhas crônicas em um sistema de garras pneumáticas de uma linha de estamparia automotiva - Pinto, Fabio Roberto Pereira (2012)
This study uses the methodology recommended the Reliability Centered Maintenance (MCC), as support for making the decision to determine the best strategy for development of maintenance plans. Such plans will be applied to a system of pneumatic clutches of a stamping line of a multinational company's auto sector. The claw is an assembly of components that form an equipment essential to the process of stamping the component parts of a car body, because its function is to hold the part during transfer from one point to another. In this particular case it holds the piece from the removal of the burden of raw materials, through the presses that give shape to the piece until the final process of filing the conveyor belt of finished product. It is during this process that there are several microparadas caused by failures claws. Despite the intervention time for correction of faults being around a few minutes, the final amount generates a significant impact on production availability. With this, a theoretical framework will be developed MCC correlating relevant concepts of maintenance and its strategic role for companies seeking excellence in its production process to meet the customer's requirements and at the same time stand out in a market increasingly fierce follow-up of parts suppliers.